Critical studies in carbon electrode materials with applications in the electroanalysis of the mycotoxin citrinin - Niland, Michael John (Rhodes University, Faculty of Science, Department of Chemistry, 2013)
Guided by increasing legislation, the analysis of food borne toxins, including mycotoxins, seeks to address market related demands for the development of analytical systems to monitor this threat to food security and human health. This Thesis is directed at the assessment of the application of electrochemistry for direct electroanalysis and characterisation of the mycotoxin citrinin (CIT) in aqueous media as well as fundamental investigations of the surface of polished and oxidised glassy carbon electrodes (GCE). This study provides the first known account of CIT detection through electrochemical methods. Although electrochemically active, CIT current responses (Ip) were highly irreproducible at polished GCE with a coefficient of variation (C.V.) of 20.16 %. As stability of Ip across multiple electrode preparations is a key requirement in electroanalysis, investigations were directed at attaining stability in CIT Ip. Achieving stability in CIT Ip was investigated via two approaches, including: accounting for Ip variability between electrode preparations as a result of variable GCE surface conditions as a post-data-acquisition analysis and secondly, removing Ip variability through modification of GCE. Accounting for variability in Ip was investigated through the application of double layer capacitance as an indicator of the activity of an electrode, and in so doing serving as a relative mediator of Ip responses between electrodes. Application of this procedure dropped CIT C.V. to a third of starting value across polished GCE (C.V. = 7.18 %), chemically oxidised GCE (Pi-GCE, C.V = 8.47 %) and functionalised multi-walled carbon nanotube modified GCE (fMWCNT, C.V. = 25.79 %) and was effective with analysis of structurally distinct molecules, 2,4-dimethylaniline (2,4-DMA) and 1,2,4-trihydroxybenzene (Triol). Furthermore, it afforded the ability to determine discreet solution overlapping data sets of Ip. Stabilising Ip through GCE surface modification was achieved by anodic electro-oxidation of GCE and allowed for direct electroanalysis of CIT and subsequent characterisation and analysis of CIT in complex media as it reduced C.V. of CIT Ip to 0.73 %. Fundamental investigations of the electrode surface condition are described such that the source of variability could be identified and the interactions of CIT with the electrode understood. Two surface oxidation techniques were applied in modification of GCE; anodic electro-oxidation (EOx GCE) and chemical oxidation using piranha solution (Pi-GCE), analysis of which has previously not been reported. Fundamental analyses to determine surface morphology and chemistry of Pi-GCE, EOx-GCE and polished GCE were conducted using high resolution scanning electron microscopy (HRSEM), scanning electrochemical microscopy (SECM), energy dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), fourier transform infrared spectroscopy (FTIR) and via electroanalytical methods. These studies showed that both oxidation procedures introduced a variety of oxide species at GCE surface, and further that the extent of those species was similar with total % O being 27.67 % and 33.47 % at Pi-GCE and EOx-GCE respectively. Although chemically similar, each surface was morphologically distinct. Electrochemical analyses at the surfaces revealed Pi-GCE to behave more similarly to polished GCE than EOx-GCE. As CIT responses were found to be stable at EOx-GCE (C.V. = 0.73 %) as opposed to Pi-GCE (C.V. = 22.87 %), stability of CIT Ip was likely to be as a result of a physical interaction with electrode morphology rather than interaction on a chemical basis. Morphological analyses revealed polished GCE and Pi-GCE to be highly morphologically irregular at the micro-scale. Although comparatively smooth, the surface morphology of EOx-GCE does not account for the stability of Ip. This study thus proposed a theory to describe the mechanism by which the limited conductivity and porosity of EOx-GCE allow for it to provide a relatively stable surface area within the oxide layer, adjacent to the electrode surface, and thus provided a stable platform for electroanalysis. Voltammetric characterization of CIT at EOx-GCE revealed that anodic oxidation in aqueous media involved an uneven number of electrons to protons via an ECE mechanism. This was illustrated to be nt = 2e- accompanied by the transfer of 1Hâ º per molecule oxidised. A proposed reaction scheme for the initial stages of CIT oxidation was suggested to involve both hydroxyl and carboxyl moieties of the CIT molecule. CIT oxidation was shown to arise as a result of a relatively complex mass transport regime which included both adsorptive and diffusive derived Ipâ‚ . The LOD in buffered aqueous media was found to be 16 nM, a highly competitive result in relation to chromatographic techniques. Further application of EOx-GCE in complex media illustrated that CIT associates non-specifically with the components of food samples, primarily proteins. As a result of this, extraction of CIT from such media is mandatory. Liquid-liquid extraction illustrated a recovery in CIT Ipâ‚ and in so doing provided a means of accurately and sensitively detecting CIT from food samples with an LOD of 20 nM. These responses were corroborated by HPLC analyses on the same extractions and illustrate the applicability of electroanalysis as an analytical technique.
Keywords: Electrodes, Carbon; Mycotoxins